Performance Enhancement of Distribution System using Grey Wolf Optimizer for Capacitor Placement and Sizing Considering Load Variations - Sahat Siagian; Yoakim Simamora; Desman Jonto Sinaga; Mas Aly Afandi (Ikatan Ahli Informatika Indonesia (IAII), 2026)
This research introduces a Grey Wolf Optimizer (GWO) strategy for determining the optimal placement and sizing of shunt capacitors in radial distribution networks under different load scenarios. The task is structured as a multi-scenario optimization model aimed at reducing active power loss, voltage deviation, and annual compensation expenses, all while adhering to bus voltage and line current limitations. Unlike traditional methods that focus on capacitor allocation for a single operating condition, this approach explicitly accounts for light, normal, and heavy load conditions to ensure solutions are effective throughout daily demand fluctuations. The method is tested on the IEEE 33-bus distribution system and benchmarked against several existing metaheuristic techniques. Findings reveal that GWO consistently provides viable capacitor configurations across all load conditions and offers enhanced technical and economic outcomes. During normal load conditions, the method decreases active power loss from 202.69 kW to 131.83 kW, and under heavy load, it achieves the highest annual net savings of 97,588. In summary, the results suggest that GWO is a reliable and economical solution for reactive power compensation planning in distribution systems with variable loads.